Anterior knee pain: As an athlete, am I at risk? (Journal of Orthopaedic & Sports Physical Therapy, 2012)
In this study, the researchers evaluated published articles using a process called a systematic review. Their initial search of the literature found 3845 possible articles of interest. These articles discussed a total of 135 possible risk factors. Based on their criteria for the review, the researchers ultimately selected 7 high-quality articles. These 7 articles analyzed 13 potential risk factors and included 243 patients who had this type of knee pain. The research team found that weakness of the quadriceps muscle, which is on the front of your thigh and helps you to straighten your knee, was predictive of developing knee pain. They also confirmed that females are at higher risk for anterior knee pain.